Assessing agricultural soil acidification and nutrient management in life cycle assessment. - Peters, Gregory M.
Purpose This paper describes part of the first detailed environmental life cycle assessment (LCA) of Australian red meat (beef and sheep meat) production. The study was intended to assist the methodological development of life cycle impact assessment by examining the feasibility of new indicators for natural resource management (NRM) issues relevant to soil management in agricultural LCA. This paper is intended to describe the NRM indicators directly related to agricultural soil chemistry. Materials and methods Three nutrient management indicators-nitrogen (N), phosphorus (P) and potassium (K) balances-were estimated on the basis of 1 kg of hot standard carcass weight (HSCW) for three grazing properties in Australia. We also examined a soil acidification indicator based on the effects of agricultural practices. Results and discussion The N balance for the grazing properties varied from a loss of 28 g N/kg HSCW to an accumulation of 170 g N/kg HSCW. For comparison, the N content of cattle is about 24 g/kg liveweight. The main contributors to these changes were the growth of N-fixing pastures (or lack thereof) and the application of fertilisers. The P and the K balances showed similar results, varying from a 3.9 g loss to a 19 g accumulation of P and a 4-g loss to a 95 g accumulation of K per kilogram HSCW. Decisions about pasture management wre also reflected in the results of the soil acidification indicator. We also identified that soil erosion at the grazing properties is a significant component of nutrient losses. Conclusions The results suggest that reducing the leaching of soil N might be the best way to balance the N budget without causing acidification. The NRM indicators developed can be benchmarked against other production systems as the application of these indicators progresses.
Keywords: LCA; Nutrient management; Red meat; Soil acidification potential